Environmental factors affecting seed germination of common teasel (Dipsacus fullonum) - Daddario, Juan Facundo Fabian (2017)
Common teasel is a widespread, invasive species that has been introduced in Buenos Aires province, Argentina, where it alters the species composition of protected areas and native grasslands. A better understanding of seed germination behavior is essential for predicting its invasion potential in new areas and would be useful for developing effective management strategies. This research, conducted under laboratory conditions, evaluated the influence of several environmental factors such as pH, constant temperature, osmotic stress, salt stress and dry storage, on germination and rate of germination of common teasel seed. Between-year variation in germination responses was also examined. Seed germination was not affected by different pH levels. Although common teasel seeds germinated over a range of temperatures from 6 to 36oC, the optimum temperature was 22oC. Common teasel seed germination showed moderate tolerance to osmotic stress and a relatively high tolerance to salt stress. No seed germination was observed at -1 MPa and 640 mM of osmotic potential and salt concentration, respectively. Seed germination remained high (> 90%) after all the dry storage treatments. Besides, the response of seeds to germination parameters showed between-year variation. It was shown that common teasel is able to germinate over a broad range of environmental conditions. This capacity would explain, at least partially, why this species is so widely distributed and its great potential to invade new areas.